Exploring Sonic Meaning and Embodiment in Human Cultural Transmission From a Pedagogical Perspective - Rinsema, Rebecca; Edwards, Jashen (Frontiers in Communication, 2021)
The authors explore how sonic material, specifically everyday sounds and songs, create and communicate personal, socio-cultural and ecological meanings. From the lulling passages of a pastoral movement streaming through a symphony hall, or the rollicking screams at stadium concerts to the roaring rhetoric and social distortions of divisive political-speak, sound and music signal frequencies and frictions at play in the human experience. Literacies are cultivated, sounds embodied and ways of sensing, knowing and being in the world are sonically communicated and established. What happens when sounds encountered in one’s everyday experience are excavated, sampled and (re)mixed? What new meanings may be derived? What old meanings might be challenged and reconstituted and reconstructed into new forms of knowing and being. What happens when songs or timeless tunes are analyzed and detangled from their ordinary meanings? How might listeners make the familiar strange and thus renew knowings? And what does any of this mean for the flux and firmness of human cultures in motion?